The leadership pipeline how to build the leadership-powered company - Charan, Ram (J-B US non-Franchise Leadership Ser, 2001)
"In this book, three experts show companies how to build their own leaders by understanding the critical passages a leader must navigate, by providing the appropriate development for navigating those passages, and by building the right system for ensuring a full pipeline of leaders now and in the future." "Together Ram Charan, Stephen Drotter, and James Noel have substantial firsthand experience in leadership succession and development around the world. They have coached some of the world's top corporate leaders and have developed effective leadership succession and development programs for leading companies of all sizes."